Development and evaluation of the control charts for variables - Ou, Yanjing. (2013)
In quality control (QC), control chart is one of the most effective tools to monitor the process and ensure the product quality. It is a powerful Statistical Process Control (SPC) method to make quick response when quality problems occur in order to avoid serious economic loss. The first objective of this PhD project is to develop new SPC techniques, for which several highly effective control charts for variables have been proposed and carefully investigated. The second task is to provide a systematic performance comparison among all typical control charts for variables including the Shewhart chart, Cumulative Sum (CUSUM) chart and Sequential Probability Ratio Test (SPRT) chart.